Analisis Kinerja Keuangan Menggunakan Du Pont System Pada PT. Wilmar Cahaya Indonesia Tbk. - Bakhtiar Ass, Syamsul; Mustafa, Mustafa; Alam Nasyirah Hanafi, Muh.; Aprilia, Putri; Abdurrahman Hadi (Al-Buhuts, 2024)
This study aims to determine the financial performance of PT. Wilmar Cahaya Indonesia Tbk in 2018-2023. This study uses a qualitative analysis method using secondary data sources with library research data collection techniques, data analysis techniques using the Du Pont system consisting of the net profit margin ratio, total asset turnover, equity multiplier, return on assets, and return on equity. The results of the study show that the financial performance of PT. Wilmar Cahaya Indonesia Tbk for the 2018-2023 period is not good. This is due to the low Return On Equity (ROE) compared to industry standards. The main underlying factor is net profit that is not comparable to the company's sales and total assets (low Net Profit Margin (NPM) and Return On Asset (ROA).